Empirical formula for the dependence of the “optical gap” value on the electron concentration Ne within the range of 10¹⁷cm⁻³ ≤Ne ≤ 10²²cm⁻³ - Fedorovich, О.А. (Вопросы атомной науки и техники, 2013)
The paper presents an empirical formula for the dependence of the “optical gap” value in the nonideal plasma radiation (absorption) spectra on Ne within the electron concentration of 10¹⁷cm⁻³ ≤Ne ≤ 10²²cm⁻³. A comparison of an empirical formula with theoretical formulas previously obtained by other authors is given. It is recommended to apply the empirical formula for determining the electron concentration by the “optical gap” value in the external layers of nonideal plasma to Ne < 10²²cm⁻³.